2011
DOI: 10.1007/s11999-010-1736-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Race/Ethnicity Differences in Hip Fracture Incidence, Morbidity, Mortality, and Function

Abstract: A PubMed literature review was performed and appropriate articles selected for inclusion in the review. WHERE ARE WE NOW?: Overall, men with hip fracture are younger, are less healthy, and have a higher postoperative mortality and morbidity. African American and Hispanics patients with hip fractures are younger than whites and have a higher incidence of fracture in men. Non-Hispanic black, Hispanic, and Asian race/ethnicity were all associated with higher odds of discharge home but a longer stay when discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
147
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(177 citation statements)
references
References 27 publications
(48 reference statements)
26
147
2
2
Order By: Relevance
“…Also, how did the comorbidity profiles differ between the two sexes? Overall, the study results corroborate trends in short-term adverse events seen after other surgical procedures, such cardiac or hip fracture surgery-with men having a higher comorbidity burden and poorer outcomes [3,4].…”
supporting
confidence: 71%
“…Also, how did the comorbidity profiles differ between the two sexes? Overall, the study results corroborate trends in short-term adverse events seen after other surgical procedures, such cardiac or hip fracture surgery-with men having a higher comorbidity burden and poorer outcomes [3,4].…”
supporting
confidence: 71%
“…Nursing home patients are in general sicker than community dwellers and the higher burden of comorbidities in men compared to women has been previously described. 19 Two published reports of the model of care in this study have shown lower TTS, LOS, and complication rate when compared to usual or standard care. 12,20 This study shows that the comorbidity burden of the patients did not affect either their TTS or their LOS.…”
Section: Discussionmentioning
confidence: 49%
“…However, it is unclear whether arthroplasty leads to better function, lower reoperation rate, and fewer complications in the long term [11]. Although there are some studies at longer term [20], including reporting results into the second decade [15], these series did not find differences between internal fixation and arthroplasty in terms of mortality. However, a meta-analysis might allow pooling of the data, which could increase the likelihood that smaller but potentially important clinical differences could be detected between treatments than is possible in individual trials.…”
Section: Introductionmentioning
confidence: 94%
“…Hip fractures often are related to osteoporosis in older patients [20]. Every year, approximately 1.6 million people worldwide sustain hip fractures.…”
Section: Introductionmentioning
confidence: 99%